Can We Rank Legal Systems According to Their Economic Efficiency? - Claude Ménard; Bertrand du Marais (Washington University Journal of Law & Policy, 2008)
Part I describes the history and methodology of the research conducted by LLSV. Part II examines the transformation of the correlation explored by LLSV into a normative approach that is illustrated particularly well by the series of reports from the International Finance Corporation (IFC— World Bank Group) on Doing Business. Part III discusses the results exposed in these reports while considering the theoretical issues involved, which have to do with whether it makes sense to rank legal systems, and procedures considered for doing so. Part IV concludes with indications about what to expect from a sound comparative approach to legal systems combining law and economics.
Keywords: Institutional economics; Ranking & amp; selection (Statistics); Economic efficiency; Law and economics (Jurisprudence); International; United States